Effectiveness of instructional media based on interactive cd learning on basic network at vocational high school : improving student cognitive ability - Doni Pernanda; Mahesi Agni Zaus; RizkyEma Wulansari; Syaiful Islami (Fakultas Ilmu Pendidikan UNP)
In the fact, students in the school were seen that most of them have low learning spirit, students were less active, because lack of using instructional media that corresponded with students characteristics in the learning process. This study aimed to know about effectiveness of instructional media based on interactive CD learning that had developed. Effectiveness test was carried out by giving pretest and posttest instruments to the students. The instruments of effectiveness was using test, and the data was processed by Independent T-test formula. Instructional media based on interactive CD learning was said effective to improve students outcomes because 87,60% students had reached Minimum Mastery Criteria. Based on the result, can be concluded that instructional media based on interactive CD learning on Basic Network was effective to use as instructional media on Basic Network learning process.